Volume 3: Biomedical and Biotechnology Engineering 2017
DOI: 10.1115/imece2017-71426
|View full text |Cite
|
Sign up to set email alerts
|

PIV and LIF Measurements in Aortic Dissection Models

Abstract: In this work an in-vitro flow experiment is conducted to elucidate the flow behavior in simplified aortic dissection (AD) disease geometries. In AD, the innermost layer of the aortic wall is locally and partially torn allowing blood to flow between the wall layers forming a parallel blood stream in what is known as the false lumen. The aim of this work is to elucidate the disease flow physics, and to provide guidance in diagnostic radiology, particularly contrast injected computed tomography (CT), where unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, Clough et al (2012) reported the presence of helical flows at different locations in the false lumen by examining images acquired with phasecontrast magnetic resonance imaging (PC-MRI) and related these helical flows to the aortic expansion rate. More recently, a few research groups are employing laser diagnostic methods to explore the haemodynamics in higher spatial and temporal resolution, using primarily particle image velocimetry (PIV) (Yip et al, 2004;Salameh et al, 2017Salameh et al, , 2019Moravia et al, 2019) and stereo-particle image velocimetry (s-PIV) (Fernandes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Clough et al (2012) reported the presence of helical flows at different locations in the false lumen by examining images acquired with phasecontrast magnetic resonance imaging (PC-MRI) and related these helical flows to the aortic expansion rate. More recently, a few research groups are employing laser diagnostic methods to explore the haemodynamics in higher spatial and temporal resolution, using primarily particle image velocimetry (PIV) (Yip et al, 2004;Salameh et al, 2017Salameh et al, , 2019Moravia et al, 2019) and stereo-particle image velocimetry (s-PIV) (Fernandes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%